2002
DOI: 10.4028/www.scientific.net/kem.230-232.467
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Physical Characterisation in the Evaluation of the Performance of Bone Allografts

Abstract: The present work compares bone allografts with synthetic hydroxyapatite regarding density, porosity, pore size distribution and phase identification. The measurement of these parameters enables a more complete knowledge of the grafts structural properties, which necessarily leads to a better selection of the most appropriate bone substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Previous studies have been shown that mineralized cancellous bone graft, as compared to demineralized cortical bone, not only reveal a higher porosity but also a wider pore size distribution, which is much more favourable for early bone regeneration. 8 On the other hand, the production of a large fracture surface area, by microfracturing the bone during morselization, they expose the bone matrix to surrounding tissues 9 and the impaction technique release bone growth factors from the cancellous bone graft.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been shown that mineralized cancellous bone graft, as compared to demineralized cortical bone, not only reveal a higher porosity but also a wider pore size distribution, which is much more favourable for early bone regeneration. 8 On the other hand, the production of a large fracture surface area, by microfracturing the bone during morselization, they expose the bone matrix to surrounding tissues 9 and the impaction technique release bone growth factors from the cancellous bone graft.…”
Section: Discussionmentioning
confidence: 99%